Ionic Homeostasis Maintenance in ALS: Focus on New Therapeutic Targets - Sirabella, Rossana; Valsecchi, Valeria; Anzilotti, Serenella; Cuomo, Ornella; Vinciguerra, Antonio; Cepparulo, Pasquale; Brancaccio, Paola; Guida, Natascia; Blondeau, Nicolas; Canzoniero, Lorella M. T.; Franco, Cristina; Amoroso, Salvatore; et al. (Frontiers in Neuroscience, 2018)
Amyotrophic lateral sclerosis (ALS) is one of the most threatening neurodegenerative disease since it causes muscular paralysis for the loss of Motor Neurons in the spinal cord, brainstem and motor cortex. Up until now, no effective pharmacological treatment is available. Two forms of ALS have been described so far: 90% of the cases presents the sporadic form (sALS) whereas the remaining 10% of the cases displays the familiar form (fALS). Approximately 20% of fALS is associated with inherited mutations in the Cu, Zn-superoxide dismutase 1 (SOD1) gene. In the last decade, ionic homeostasis dysregulation has been proposed as the main trigger of the pathological cascade that brings to motor-neurons loss. In the light of these premises, the present review will analyze the involvement in ALS pathophysiology of the most well studied metal ions, i.e., calcium, sodium, iron, copper and zinc, with particular focus to the role of ionic channels and transporters able to contribute in the regulation of ionic homeostasis, in order to propose new putative molecular targets for future therapeutic strategies to ameliorate the progression of this devastating neurodegenerative disease.